The GALAH survey: accurate radial velocities and library of observed stellar template spectra. Issue 1 (23rd August 2018) - Zwitter, Tomaž; Kos, Janez; Chiavassa, Andrea; Buder, Sven; Traven, Gregor; Čotar, Klemen; Lin, Jane; Asplund, Martin; Bland-Hawthorn, Joss; Casey, Andrew R; De Silva, Gayandhi; Duong, Ly; et al.
ABSTRACT: GALAH is a large-scale magnitude-limited southern stellar spectroscopic survey. Its second data release (GALAH DR2) provides values of stellar parameters and abundances of 23 elements for 342 682 stars (Buder et al.). Here we add a description of the public release of radial velocities with a typical accuracy of 0.1 km s −1 for 336 215 of these stars, achievable due to the large wavelength coverage, high resolving power, and good signal-to-noise ratio of the observed spectra, but also because convective motions in stellar atmosphere and gravitational redshift from the star to the observer are taken into account. In the process we derive medians of observed spectra that are nearly noiseless, as they are obtained from between 100 and 1116 observed spectra belonging to the same bin with a width of 50 K in temperature, 0.2 dex in gravity, and 0.1 dex in metallicity. Publicly released 1181 median spectra have a resolving power of 28 000 and trace the well-populated stellar types with metallicities between −0.6 and +0.3. Note that radial velocities from GALAH are an excellent match to the accuracy of velocity components along the sky plane derived by Gaia for the same stars. The level of accuracy achieved here is adequate for studies of dynamics within stellar clusters, associations, and streams in the Galaxy. So it may be relevant for studies of the distribution of dark matter.